(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
The calculation of design loads on offshore wind turbine structures is a complex process. So, this thesis is performed to study and investigate the influence of environmental conditions on hydrodynamic loading acting on foundations of fixed offshore wind turbine. For this purpose, (5-MW) NREL monopile foundation was chosen. The foundation of wind turbine was tested at the intermediate water region with water depth (25m). The dimensions of the foundation and water depth beside wave properties were modelling by using Froude relationships with scale ratio (1:100). Two-dimensional (regular) and non-breaking waves were tested. Morison equation for non-diffracting case was used and programmed by using (C++) language to compute the wave forces. This equation delivers the sum of drag and inertia force. Inertia force is proportional to acceleration wave particle while the drag force is related with the velocity particle. The two coefficients of equation ( , ), inertia and drag respectively are estimated according to Det Norske Veritas (DNV) standard. A classical linearized wave theory has been developed by Airy based in this paper, this theory has been used to estimate the kinematics properties (velocities and accelerations) of the wave particles. Numerically, the wave will simulate by using (AQWA) solver in (ANSYS-19.0) workbench. It was shown that the wave forces is related with the height and frequency of wave, it is increase when one or both of wave height and wave frequency increase.